Ecology, Morphology and Molecular Confirmation of Chaetogaster limnaei (Annelida: Naididae) retrieved from freshwater snail Physa acuta from Greater Zab River, Iraq - Shwan Khursheed Bashê (Tikrit Journal of Pure Science, 2023)
The present study is concerned with the Chaetogaster limnaei retrieved from the freshwater snail Physa acuta collected from (March-October 2021) from various locations near Chama-dubz village on the Greater Zab River, Erbil province, Iraq. Some Physicochemical variables, like water temperature, pH, Dissolved Oxygen, and Calcium ion experiment on a freshwater snail. The result showed statistically significant differences among Monthly variations with variables (number of snails, water temperature, pH and DO, and Calcium ion). In addition, isolated the Chaetogaster limnaei from Physa acuta with a prevalence was 5.75% (33/574), which has no dorsal and ventral chaeta approximately 14 to 20 per bundle, lack in segments 3 to 5, and chaetae and a vestige of a prostomium with sharply bent teeth. The identified morphologically and molecularly confirmed by using a COI sequence marker confirmed a 100% match to species with accession number (KF952336.1). As a result, the current study is the first report of Chaetogaster limnaei in Iraq, supported by phylogenetic analysis using Maximum Likelihood and Maximum Parsimony Methods.